Charge Ordering in Cobalt Oxides: Impact on Structure, Magnetic and Transport Properties1. Issue 8 (14th April 2015) - Raveau, Bernard; Seikh, Md. Motin
Abstract: This review shows the great impact of charge ordering upon the magnetic and transport properties of mixed valent Co 4+ /Co 3+ and Co 3+ /Co 2+ cobalt oxides. The relationships between charge ordering and physical properties are described for three structural families: the ordered oxygen deficient perovskites and the Ruddlesden and Popper (RP) derivative La1.5 Sr0.5 CoO4, the layered Na x CoO2 series and the "114" CaBaCo4 O7 oxide. Abstract :